A three-dimensional thermal analysis for cooling a square Light Emitting Diode by Multiwalled Carbon Nanotube-nanofluid-filled in a rectangular microchannel - Mohamed Bechir Ben Hamida (SAGE Publishing, 2021)
The aim of this paper is to ensure proper thermal management in order to remove and dissipate the heat produced by a square Light Emitting Diode (LED), as well as to ensure stable and safe operation by reducing the junction temperature. For this, we developed a three-dimensional code, time-dependent that solves the systems of equations for the mass, momentum, and energy using Comsol Multiphysics. After validation of this numerical 3D code, the thermal performance of a LED cooling system with three nanofluids such as MWCNT-Water, MWCNT-Ethylene Glycol, and MWCNT-Engine oil is studied numerically into account of aggregation effect. Several parameters such as: the power of the LED lamp, the inlet temperature and velocity of nanofluid, the length of the heat sink, and the length of the microchannel have been varied in order to find an optimal condition allowing a good heat dissipation from the LED chip to the heat sink. It was concluded that the use of MWCNT-Water in the microchannel is the best nanofluid that can cool the heat sink. In addition, the increase of velocity inlet of the coolant in the microchannel, the length of the heat sink, and the microchannel length while the decrease of the inlet temperature of nanofluid in the microchannel are an important factors allowing the decrease of the junction temperature of the square LED lamp.